2021
DOI: 10.1111/bjso.12490
|View full text |Cite
|
Sign up to set email alerts
|

‘A police officer shot a Black man’: Racial categorization, racism, and mundane culpability in news reports of police shootings of black people in the United States of America

Abstract: The current socio-political circumstances in the United States (US), constituted by the increasing visibility of police shootings of Black people, present a compelling moment for analysing how news media report about law enforcement, culpability, and racism. This paper conducts a membership categorization analysis of recent news media reports of police shootings of Black people (May 2020-October 2020) and investigates how news media negotiate culpability of agents involved these shootings. Findings illustrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…For participants, the then race was mobilized in relation to national categories in making claims about racism. Shrikant and Sambaraju (2021) examine the use of racial categorizations in news announcements involving police killings of Black persons. In the ongoing context of increased attention to police violence on Black persons, racial categorization in announcing such events takes on distinct meanings.…”
Section: Mobilizing Racementioning
confidence: 99%
See 1 more Smart Citation
“…For participants, the then race was mobilized in relation to national categories in making claims about racism. Shrikant and Sambaraju (2021) examine the use of racial categorizations in news announcements involving police killings of Black persons. In the ongoing context of increased attention to police violence on Black persons, racial categorization in announcing such events takes on distinct meanings.…”
Section: Mobilizing Racementioning
confidence: 99%
“…The absence of any other reason leaves no explanation for the shooting and indicates the possibility of racism. Shrikant and Sambaraju (2021) suggest that this is all the more likely given the increasing awareness that Black persons in the United States are routine targets of police violence. Race and racial categorization then are used to imply institutionalized racial violence.…”
Section: Mobilizing Racementioning
confidence: 99%
“…Discursive psychologists and conversation analysts have investigated the denials of racism and debates about race‐related affairs (Augoustinos & Every, 2007; Durrheim et al, 2015; Wetherell & Potter, 1992), and the situated deployments of race categories (Shrikant, 2022; Shrikant & Sanbaraju, 2021; Whitehead, 2009, 2012, 2013, 2019) in various interactional settings (see commentaries and reviews by Durrheim, 2014; Gibson, 2021; Robles & Shrikant, 2021; Whitehead, 2017). Recent investigations have turned to racism at the point of its production (Bolden et al, 2022; Joyce & Sterphone, 2022; Laurier et al, Under Review).…”
Section: Introductionmentioning
confidence: 99%
“…This is evident in law enforcement's contentious history of fatal shootings; none more so than in jurisdictions such as the Philippines, which has seen some of the highest numbers of officer-involved shootings (OIS) (Amnesty International, 2017; Jensen and Hapal, 2018; Tusalem, 2019), and Brazil where shooting figures have remained high (United Nations, 2022). Much of the criticism of such practices originates in Europe (European Parliament, 2016) and the United States (US State Department, 2023a, 2023b) where OIS incidents have been linked to institutional racism (Mesic et al, 2018; Shrikant and Sambaraju, 2021). In 2022, statistics for the United Kingdom (UK) indicated that its officers were three times more likely to use force on Black people than on any other race (Home Office, 2022), and in 2023 the UK’s premier police force was found to be institutionally racist, sexist and misogynistic (Baroness Casey Review, 2023).…”
Section: Introductionmentioning
confidence: 99%